Levels of Total Cholesterol and Triglycerides in Type 2 Diabetic Sudanese Patients - Hamza, Mohammed Abdelrhim; Abdallah, Badr Eldin Elsonni; Ali, Khalid Eltom (Gezira Journal of Health Sciences; Vol 8 No 1 (2012), 2012)
Introduction: Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycaemia with disturbances of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action, or both. (1) Objectives This study aimed to estimate the levels of total cholesterol and triglycerides as control  markers of type 2 diabetes mellitus in Sudanese patients. Methods: Seventy Sudanese controlled NIDDM patients of age 42-80 years and of diabetes duration 1-27 years, 30  non diabetic subjects age and sex-matched taken as a control group. Fasting blood glucose, total cholesterol, and triglycerides (TG) were measured and the results obtained were statistically analysed. Results : There were no statistically significant differences between diabetic group and control group observed in TG levels.  The total cholesterol in the diabetic group showed significant increase than the control group (P=0.04), also this study showed, 64.3% of the diabetic group had FBG>140mg/dl , 24.3% had cholesterol level >240 mg/dl and 9% had Triglycerides level >200 mg/dl. Conclusion: This study suggests the need for improving glycemic control in Sudanese diabetic patients, that might lead to  improvement in lipid values and decrease the diabetes-associated complications. الملخص: هدفت  هذه الدراسة لاستخدام التقييم الكيموحيوي لضبط مستوى السكر عند مرضي السكري غير المعتمدين علي الانسولين مقارنه مع أصحاء من نفس النوع والعمر. إشتملت هذه الدراسه علي 100 شخص منهم 70 مريضا بالسكري غير المعتمدين علي الانسولين تتراوح أعمارهم بين 42-80 عاما وتمتد فترة مرضهم بين 1- 27   عاما و30 أصحاء من نفس النوع والعمر . تضمنت هذه الدراسه  القياسات الكيموحيويه الأتيه: سكر دم الصائم، الكوليستيرول ، ثلاثي أسيل الجليسرول ومؤشر كتلة الجسم وحللت النتائج تحليلا إحصائيا.   اظهرت الدراسة عدم وجود  إختلاف ذو معني بين مجموعة مرضي السكري ومجموعة الأصحاء في مستويات ثلاثي أسيل الجليسرول بينما وجد تركيز كل من سكر دم الصائم و الكوليستيرول الكلى مرتفعا إرتفاعا ذا معني عند مجموعة مرضي السكري. مستوي الكوليستيرول اظهر إرتباطا موجبا مع ثلاثي أسيل الجليسرول.   طبقا لتقسيم جمعية مرضى السكري العالميه الأمريكيه أظهرت هذه الدراسه أن نسبة 35.7  يتميزون بدرجة ضبط جيدة (معدل قياس  سكر دم الصائم لديهم أقل من 140مج/ملتر) بينما 75.7% يتميزون بدرجة ضبط جيدة للكوليستيرول (مستوي الكوليستيرول لديهم أقل من  240مج/ملتر) و91% يتميزون بدرجة ضبط جيدة لثلاثي أسيل الجليسرول (مستوي ثلاثي أسيل الجليسرول لديهم أقل من  200مج/ملتر). وعليه يعتبر ان بعض   هؤلاء المرضى غير متمتعين بدرجة ضبط جيده لمرض السكري.